2014
DOI: 10.1039/c4dt01187b
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent monocyclometalated cationic gold(iii) complexes: synthesis, photophysical characterization and catalytic investigations

Abstract: Stable, luminescent, and cationic monocyclometalated gold(iii) monoaryl complexes of the type [(ppy)Au(FMes)(L)](+)[OTf](-) [L = 4-phenylpyridine (), quinoline (), 4-fluoroaniline (), P(OMe)3 (), PPh3 ()], bearing different ancillary ligands, synthesized starting from the precursor complex [(ppy)Au(FMes)(OH2)](+)[OTf](-) () are reported. The preliminary assignment of the structure of the complexes by various nuclear magnetic resonance spectroscopy techniques and elemental analysis has been further corroborated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…[78] Ther eaction of lithiated 2,4,6-tris(trifluoromethyl)phenyl (LiFMes) with the Au III -dichloro complex 56 in dry diethyl ether afforded the monoarylated product 76 in 77 %y ield. [79] Photoluminescence emission quantum yields of 30 %(l = 441 nm) in solution and 39 %(l = 622 nm) in the solid state could be recorded, which are comparable to those of the most efficient C^N^C biscyclometalated Au III complexes described in the previous Sections.…”
Section: [(C^n)au(aryl)] Complexessupporting
confidence: 81%
“…[78] Ther eaction of lithiated 2,4,6-tris(trifluoromethyl)phenyl (LiFMes) with the Au III -dichloro complex 56 in dry diethyl ether afforded the monoarylated product 76 in 77 %y ield. [79] Photoluminescence emission quantum yields of 30 %(l = 441 nm) in solution and 39 %(l = 622 nm) in the solid state could be recorded, which are comparable to those of the most efficient C^N^C biscyclometalated Au III complexes described in the previous Sections.…”
Section: [(C^n)au(aryl)] Complexessupporting
confidence: 81%
“…Complexes 3 – 6 were prepared as previously described 33. 34 Complex 2 ([(ppy)Au(FMes)(TFA)]; ppy=2‐(phenyl)pyridine, FMes=1,3,5‐tris(trifluoromethyl)benzene, TFA=trifluoroacetic acid) was synthesized in a manner similar to a method reported by Zehnder et al 34. Treatment of the previously reported [(ppy)Au(FMes)Cl]34 with a slight excess of silver trifluoroacetate in dichloromethane at room temperature for 21 h gave the desired product 2 in 97 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…34 Complex 2 ([(ppy)Au(FMes)(TFA)]; ppy=2‐(phenyl)pyridine, FMes=1,3,5‐tris(trifluoromethyl)benzene, TFA=trifluoroacetic acid) was synthesized in a manner similar to a method reported by Zehnder et al 34. Treatment of the previously reported [(ppy)Au(FMes)Cl]34 with a slight excess of silver trifluoroacetate in dichloromethane at room temperature for 21 h gave the desired product 2 in 97 % yield. 1 H NMR studies revealed a diagnostic upfield shift of Δ δ =−0.7 ppm relative to the precursor complex [(ppy)Au(FMes)Cl], for the proton in the α position relative to the nitrogen atom of the cyclometalating ppy ligand to δ =8.82 ppm, upon coordination of the new ligand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations